Mental illness on Instagram: a mixed method study to characterize public content, sentiments, and trends of antidepressant use. (4th July 2021) - Gupta, Rohit; Ariefdjohan, Merlin
Abstract: Background: Individuals with mental illness use social media to share treatment experiences and anecdotal information. Despite the significant impact of social media on individuals with mental illness, posts related to antidepressants have not been studied systematically. Aims: This study evaluates public sentiments and content posted on Instagram regarding the use of antidepressants. Methods: Instagram posts from July 2010 to June 30, 2018 containing hashtags of commonly prescribed antidepressants and anxiety/depression-related terms were gathered ( n = 13, 096). Approximately 1, 000 posts were randomly selected and evaluated for photo content, anecdotal experiences, sentiments towards antidepressants, and mentions of psychotherapy, comorbidities, polypharmacy, or adverse effects. Results: Instagram posts describing antidepressant use have increased exponentially from 2010, and 43% provided anecdotal experiences. Among these posts, 58% expressed negative sentiments towards antidepressant usage, citing adverse effects and lack of improvement. Posts that also mentioned psychotherapy, comorbidities, or polypharmacy differed in their collective sentiments. Misinformation was present in analyzed posts, and none mentioned recovery-oriented materials (i.e., mental health facility, hotline, etc.). Conclusions: Instagram is a useful resource for exploring public sentiments related to antidepressant use. Mental health professionals should be cognizant of these sentiments/perceptions in order to tailor communication with patients and should consider increasing their social media presence.